발열 환아 보호자의 응급실 방문 횟수에 영향을 미치는 요인 - 김민애(Kim, Minae); 김나현(Kim, Nahyun) (Journal of Korean biological nursing science, 2022)
Purpose: This study aimed to identify factors affecting the number of emergency department visits by caregivers of children with fever. Methods: Data were collected from 145 caregivers whose children aged six or less with two or more emergency department visits annually mainly because of fever. Collected data were analyzed with descriptive frequency analysis, independent t-test, Fisher exact, one-way ANOVA, Scheffé test, Dunnett T3, Pearson's correlation, and stepwise multiple regression using SPSS 25.0 software. Results: Regression analysis results revealed that among factors influencing the number of emergency department visits by caregivers of children with fever were state anxiety (β= .35, p= .009), self-efficacy (β= -.29, p= .029), and gestational age of the children (β= .17, p= .010). These variables had an explanatory power of 42.3% concerning the number of emergency department visits. Conclusion: Our findings revealed that caregivers' level of state anxiety and self-efficacy were major factors influencing the number of emergency department visits. It is expected that providing education concerning fever and emotional support for caregivers of children with fever can relieve their anxiety and enhance their self-efficacy levels, which in turn may reduce the number of unnecessary emergency department visits of children with fever and ultimately address the issue of over-crowding in emergency department.